Relationship Between Metabolic Syndrome and Familial History of Hypertension/Stroke, Diabetes, and Cardiovascular Disease - Paek, Kyung Won (The Korean Academy of Medical Sciences, 2006)
This research analyzes the prevalence of metabolic syndrome (MS) in Korea and examines how the presence of a familial history of diseases related to MS, such as hypertension/stroke, cardiovascular disease, and diabetes, affect the development of MS in Koreans. The prevalence of MS and its components, as defined by the National Cholesterol Education Program Adult Treatment Panel guidelines, were evaluated in nationally representative samples of non-institutionalized civilian Koreans. This analysis is based on the 2001 Korea National Health and Nutrition Examination Survey, which used a stratified multistage probability sampling design. The final study included 5,742 adults who had completed the necessary health examinations and met the diagnosis of MS. The prevalence of MS was 25.5% in men and 28.7% in women. Odds ratio for MS among men with a familial history of hypertension/stroke was higher than that among men who did not have this history. The OR for MS among women with a familial history of hypertension/stroke or diabetes was higher than that among women who had no familial history of these diseases. These results show that familial history of hypertension/stroke and diabetes was significantly related to the presence of MS in both young men and women.